Green health : an A-to-Z guide - Ogunseitan, Oladele (Sage reference series on green society.)
"Green Health: An A-to-Z Guide examines the green movement within the contexts of personal health and the healthcare industry, focusing on consumer lifestyles and how they affect resource conservation, pollution prevention, and environmental management. The scope of the title involves the societal goals of protecting human health and reducing the ecological footprint of healthcare. With approximately 150 signed entries written from global viewpoints by university professors and experts, Green Health: An A-to-Z Guide explores topics ranging from ecologically sustainable pharmaceuticals to the health risks of fossil fuels, biological stressors, the precautionary principle and wellness, organic food and health, hazardous waste, drinking water, the greening of healthcare, and more. Vivid photographs, searchable hyperlinks, numerous cross references, an extensive resource guide, and a clear, accessible writing style make the Green Society ideal for classroom use as well as for research"--